Pandemic scientific data sharing recommendations: examining and re-imagining pre-print servers after the end of the world-wide emergency - Shira Doron; Westyn Branch-Elliman (Antimicrobial Stewardship & Healthcare Epidemiology, 2023)
Early in the pandemic, pre-print servers sped rapid evidence sharing. A collaborative of major medical journals supported their use to ensure equitable access to scientific advancements. In the intervening three years, we have made major advancements in the prevention and treatment of COVID-19 and learned about the benefits and limitations of pre-prints as a mechanism for sharing and disseminating scientific knowledge.